Performance of high wokability slag-cement mortar for ferrocement - Memon, Noor Ahmed; Sumadi, Salihuddin Radin; Ramli, Mahyuddin (Elsevier Science B.V., Amsterdam, 2007)
The performance of high workability mortar mix, applicable for the casting of thin ferrocement elements by using slag as cement replacement and superplasticizer as water reducing agent is investigated. Cement mortars (1:2. 1:2.5 and 1:3) incorporating various percentages of slag and superplasticizer were designed to have high workability (136Â±3% flow). Performance of the mortars is studied in terms of compressive strength, unit weight, strength development and water absorption. Effect of three different curing regimes on strength and strength development of the mortars is also the part of this study. The results showed that the high workability slag cement mortars of reasonably high strength, low water absorption and exhibiting early age strength comparable to that of the OPC mortars can be designed in order to cast thin ferrocement elements by the method of pouring.